2020
DOI: 10.1089/cbr.2019.3179
|View full text |Cite
|
Sign up to set email alerts
|

Laminarin from Seaweed (Laminaria japonica) Inhibits Hepatocellular Carcinoma Through Upregulating Senescence Marker Protein-30

Abstract: Objective: This study aimed at investigating the specific roles of laminarin from seaweed (Laminaria japonica) in hepatocellular carcinoma (HCC) and its potential mechanisms related to senescence marker protein-30 (SMP-30). Materials and Methods: Human HCC cell lines, including Bel-7404 and HepG2, were incubated with different concentrations of laminarin (0, 5, 15, 25, 35, and 45 mg/mL). The cell viability and apoptosis rates were detected by WST-8 cell proliferation assay and flow cytometry, respectively. Hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Laminarin possesses a wide range of biological activities, including antitumor, antioxidant, anti-inflammatory, and other biofunctional activities [70,74]. Lin Tian et al evaluated the antitumor roles of laminarin from seaweed (Laminaria japonica) [127]. The results showed that laminarin significantly inhibited the proliferation and promoted the apoptosis of BEL-7404 and HepG2 cells in vitro, and it also significantly inhibited the growth of the tumor in Hepa 1-6 tumor-bearing mice [127].…”
Section: Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Laminarin possesses a wide range of biological activities, including antitumor, antioxidant, anti-inflammatory, and other biofunctional activities [70,74]. Lin Tian et al evaluated the antitumor roles of laminarin from seaweed (Laminaria japonica) [127]. The results showed that laminarin significantly inhibited the proliferation and promoted the apoptosis of BEL-7404 and HepG2 cells in vitro, and it also significantly inhibited the growth of the tumor in Hepa 1-6 tumor-bearing mice [127].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Lin Tian et al evaluated the antitumor roles of laminarin from seaweed (Laminaria japonica) [127]. The results showed that laminarin significantly inhibited the proliferation and promoted the apoptosis of BEL-7404 and HepG2 cells in vitro, and it also significantly inhibited the growth of the tumor in Hepa 1-6 tumor-bearing mice [127]. The regulatory mechanism of Laminaria in tumors is to increase the expression of senescence marker protein-30 (SMP-30) in BEL-7404 and HepG2 cells.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…(dashima) has been proven to exert cytotoxic activity against various cancer types including breast, colon, hepatocellular, lung, and prostate cancer cells, by inhibiting proliferation and inducing apoptosis via both mitochondrialdependent and death receptor rough extrinsic-related pathways [25][26][27][28][29][30]. In addition, similar anticancer effects have been reported for bioactive compounds extracted from Laminaria japonica, such as glycoproteins, polysaccharides, laminarin, fucoxanthin, and phlorotannin [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, Hizikia fusiforme inhibited EJ tumor growth both in vivo and in vitro through G1-phase cell cycle arrest by downregulating cyclins and cyclin-dependent kinases (CDKs), as well as by inhibiting the expression of MMP-9 by downregulating NF-κB, AP-1, and Sp-1 [122]. In addition, seaweed extract also exhibited potent anticancer activity against hepatocellular carcinoma (HCC) cell lines [123], the U87MG cell line [129], and sarcoma 180 ascites tumor cells both in vitro and in vivo [126]. Furthermore, the inhibition of HT-29 cell proliferation by fucoidan may be due to the downregulation of IGF-IR signaling by the main IRS-1/PI3K/AKT pathway.…”
Section: Sulfated Heterorhamnansmentioning
confidence: 99%